Preparation of ordered silver angular nanoparticles array in block copolymer film for surface-enhanced Raman spectroscopy; Journal of Nanoparticle Research; Vol. 18, iss. 10 - Svanda J. Jan; Gromov M. V. Maksim Valerjevich; Kalacheva E. S. Evgeniya Sergeevna; Postnikov P. S. Pavel Sergeevich; Svorcik V.; Lyutakov O. Oleksy (2016, 2016)
Title screen